Pengembangan Media Pembelajaran Berbasis Smartboard pada Kelas VIII dalam Pembelajaran IPS di SMP Negeri 4 Kubung - Jannah, Miftahul; Basyirun, Fajri; Putri, Desi Armi Eka (Indo-MathEdu Intellectuals Journal, 2026)
Social Studies learning in the eighth-grade curriculum at SMP Negeri 4 Kubung requires active participation and the ability of students to engage dynamically with social phenomena. However, traditional teaching methods still dominate, leading to a more passive approach among students, despite the availability of technological resources such as smartboards at school. This study aims to create a smartboard-based learning media to facilitate interactive and collaborative learning experiences for eighth-grade students at SMP Negeri 4 Kubung. This study uses a Research and Development (R&D) methodology with the ADDIE model. This study focuses on class VIII.2 and social studies teachers. Data collection techniques include observation, interviews, expert validation questionnaires for content, media, and language, and a practicality response survey. The results show that the developed smartboard-based learning media is categorized as highly valid based on expert assessments. The practicality test shows that both teachers and students consider the media very practical. The use of this media has been proven effective in increasing active participation and enthusiasm for learning among students through its interactive features. Future researchers are advised to develop similar smartboard media for other eighth-grade social studies materials such as social dynamics or globalization.